Effects of anti-inflammatory treatment on efficacy of selective laser trabeculoplasty: a systematic review and meta-analysis. Issue 12 (2nd December 2021) - Chen, Yu-Sheng; Hung, Hai-Ting; Guo, Siao-Pei; Chang, Hua-Ching
ABSTRACT: Background: Selective laser trabeculoplasty (SLT) can evidently reduce intraocular pressure (IOP) in cases of open-angle glaucoma. Several studies have investigated the effectiveness of anti-inflammatory treatment to relieve discomfort after SLT, but whether such treatments affect the response of SLT remains uncertain. Methods: We systematically searched PubMed, Embase, Web of Science, and Cochrane Library for relevant studies published before 31 March 2021. The major outcomes were the efficacy of post-SLT anti-inflammatory treatment on IOP reduction, incidence of discomfort, and anterior chamber inflammation compared with those of placebo agents. Results: Five randomized controlled trials with 235 eyes receiving anti-inflammatory treatment and 170 eyes receiving placebo agents were included in the meta-analysis. Compared with placebo, no significant differences were present in IOP reduction effects upon using topical non-steroidal anti-inflammatory drugs or steroid post-SLT. The results were consistent from 1 to 6 months during follow-up. Furthermore, anti-inflammatory treatment had no significant effects on pain or discomfort or the presence of anterior chamber cells 1 h to 1 week post-SLT. Conclusion: Topical anti-inflammatory treatment after SLT for patients with glaucoma neither significantly affected IOP reduction nor remarkably relieved clinical discomfort and anterior chamber inflammation. Hence, regular use of post-SLT anti-inflammatory treatment may be unnecessary.